Monetary Policy Transmission and Credit Allocation to Productive Sectors in Indonesia - Ardian Pratama; Mei Sulfia Nurinda (Economics Note, 2026)
Monetary policy transmission plays a crucial role in shaping credit allocation and economic performance in emerging economies. Indonesia provides a relevant case due to its bank dominated financial system and long standing reliance on interest rate based monetary instruments. This study examines how monetary policy transmission mechanisms influence credit allocation to productive sectors in Indonesia. The research adopts a qualitative empirical synthesis supported by prior econometric evidence from Vector Autoregression, panel data, and impulse response studies. The analysis focuses on key transmission channels including interest rates, bank lending, asset prices, and inflation expectations. The findings show that the interest rate and bank lending channels significantly affect investment credit distribution to productive sectors such as manufacturing, agriculture, and services. However, transmission effectiveness varies across bank size, capitalization, and economic periods. Large banks exhibit weaker credit responses to policy shocks, while smaller banks transmit policy signals more effectively. Asset price and expectation channels influence inflation dynamics but show limited direct impact on sectoral credit allocation. The study concludes that monetary policy effectiveness in Indonesia depends on institutional banking characteristics and policy credibility. Strengthening financial intermediation and improving transmission speed are essential to enhance productive sector financing and sustain long term economic growth.